An Analysis the Factor of Wife Support Toward Smoking Behavior of the Husband in a Boarding Room RT 14 Ketegan Timur Taman District Sidoarjo Regency - Jihan Ayu Alip Pristananda; Siti Farida Noor Layla (Universitas STRADA Indonesia, 2021)
Cigarettes are still one of the main health problems in the world. Cigarette smoke is not only harmful to the smoker himself, but also affects the people around him. In Indonesia number of smokers are quite high which is potentialy harms the other people's health. Mental support from the sibblings are take important role toward smoking behavior and effort to push down the smoking desire. Thus, this study aims to analyze the effect of wife's support on behavior in the boarding house RT 14 Ketegan Timur, Taman District, Sidoarjo Regency.The study was conducted in July 2020 with a research design using a cross sectional method. A sample of 55 housewives who live in the boarding rooms with their husbands who have a smoking habit were taken using purposive total sampling technique. The research was conducted by filling out a questionnaire and the data were processed using the Ordinal Regression Test.The results of this study indicate that the wife's support for the husband's smoking behavior is mostly in the moderate category, namely 35 respondents or 64% of the total respondents. Meanwhile, the husband's smoking behavior in the moderate category was 30 respondents or 55% of the total respondents. There is an influence between the wife's support on the husband's smoking behavior. This can be seen from the significant value of 0.000 (<0.05) and the coefficient value of the wife's support variable is positive, this shows that the wife's support has an undirectional relationship with smoking behavior. By giving support from the wife for the husband can change his smoking behavior in their boarding house and reduce the smoking intensity of smoking cigarette and in case probably to stop.